Specialized Pro-resolving Lipid Mediators: Modulation of Diabetes-Associated Cardio-, Reno-, and Retino-Vascular Complications - de Gaetano, Monica; McEvoy, Caitriona; Andrews, Darrell; Cacace, Antonino; Hunter, Jonathan; Brennan, Eoin; Godson, Catherine (Frontiers in Pharmacology, 2018)
Diabetes and its associated chronic complications present a healthcare challenge on a global scale. Despite improvements in the management of chronic complications of the micro-/macro-vasculature, their growing prevalence and incidence highlights the scale of the problem. It is currently estimated that diabetes affects 425 million people globally and it is anticipated that this figure will rise by 2025 to 700 million people. The vascular complications of diabetes including diabetes-associated atherosclerosis and kidney disease present a particular challenge. Diabetes is the leading cause of end stage renal disease, reflecting fibrosis leading to organ failure. Moreover, diabetes associated states of inflammation, neo-vascularization, apoptosis and hypercoagulability contribute to also exacerbate atherosclerosis, from the metabolic syndrome to advanced disease, plaque rupture and coronary thrombosis. Current therapeutic interventions focus on regulating blood glucose, glomerular and peripheral hypertension and can at best slow the progression of diabetes complications. Recently advanced knowledge of the pathogenesis underlying diabetes and associated complications revealed common mechanisms, including the inflammatory response, insulin resistance and hyperglycemia. The major role that inflammation plays in many chronic diseases has led to the development of new strategies aiming to promote the restoration of homeostasis through the “resolution of inflammation”. These strategies aim to mimic the spontaneous activities of the ‘specialised pro-resolving mediators’ (SPMs), including endogenous molecules and their synthetic mimetics. This review aims to discuss the effect of SPMs [with particular attention to Lipoxins (LXs) and Resolvins (Rvs)] on inflammatory responses in a series of experimental models of diabetic complications, as well as evidence from human studies, in the context of cardio- and reno-vascular diabetic complications, with a brief mention to diabetic retinopathy (DR). These data collectively support the hypothesis that endogenously generated SPMs or synthetic mimetics of their activities may represent lead molecules in a new discipline, namely the ‘resolution pharmacology’, offering hope for new therapeutic strategies to prevent and treat, specifically, diabetes-associated atherosclerosistic, and diabetic nephropathy and retinopathy.